Broad-spectrum quorum sensing and biofilm inhibition by green tea against gram-negative pathogenic bacteria: Deciphering the role of phytocompounds through molecular modelling. (January 2019) - Qais, Faizan Abul; Khan, Mohammad Shavez; Ahmad, Iqbal
Abstract: The emerging prevalence of multidrug-resistance in Gram-negative pathogens, due to conventional antimicrobial therapeutics, has led the researchers to emphasize on development of alternative novel strategies to suppress the bacterial virulence and pathogenicity through inhibition of quorum sensing (QS) and biofilms. QS is a bacterial communication system to produce density-dependent response via chemical signalling that controls pathogenesis and biofilms formation. Leaves of green tea are used worldwide as beverage which is also known for its broad-spectrum therapeutic efficacy. In this work, we have identified and characterized the most bioactive faction of green tea extract and evaluated the anti-QS and antibiofilm activity of green tea ethyl acetate fraction (GTEF) i.e. most active fraction, on three different Gram-negative bacterial pathogens. GTEF inhibited the violacein production by >75% in C. violaceum 12472. Many virulence factors of P. aeruginosa PAO1 viz. pyocyanin, pyoverdin, exoprotease, elastase, rhamnolipid production, and swimming motility were remarkably reduced in presence of sub-MICs of GTEF. Moreover, prodigiosin, protease activity, cell surface hydrophobicity, and swimming of S. marcescens MTCC 97 were also decreased significantly by the supplementation of GTEF in culture media. GTEF exhibited broad-spectrum antibiofilm action with >80% reduction in biofilm formation of test pathogens. In silico studies gave a mechanistic insight of action of GTEF. Molecular modelling revealed that phytoconstituents detected by GC/MS exhibited affinity (in order of 10 4  M −1 ) towards AHL synthases (LasI and EsaI). The molecular binding between phytocompounds and receptor proteins (LasR, RhlR, and PqsR) of QS circuit was also energetically favourable (ΔG°≥ 5.0 kcal mol −1 ) and supported by hydrogen bonds and hydrophobic interactions. These compounds were found to be docked in ligand binding domain of CviR and occupied same cavity as that of its antagonist. Squalene and thunbergol interacted with LasA at tartaric acid binding pocket and the complex was strengthened with binding energy −5.9 kcal mol −1 . Moreover, interaction of thunbergol with biofilm-associated proteins viz. PilT and PilY1, might be disabling the pilus assembly and consequently inhibiting biofilm formation. In vivo validation of results suggested the protective role GTEF against QS-mediated pathogenicity and it might become a novel non-antibiotic QS inhibitor to control bacterial infection. Graphical abstract: Highlights: This is the first report of broad-spectrum QS and biofilm inhibition by green tea against Gram -ve bacterial pathogens. Further dissection crude methanolic extract was performed for enrichment to obtain better activity than previous findings. The in vivo validation of therapeutic efficacy of extract was also confirmed. In silico studies gave the closer insights regarding its mode of action.